Analysis of the Influence of Social Media Marketing on Purchase Decisions in Limited Market Pharmacies with Digital Literacy as a Moderating Variable - Rena Wida Arias; Endi Sarwoko; Cosmas Gatot Haryono (Dinasti Review, 2025)
This study aims to analyze the influence of social media marketing on consumer purchase decisions in pharmacies operating in limited market areas, and to evaluate the moderating role of digital literacy. The research is motivated by stagnant sales performance at Laris Farma Pharmacy in Blitar Regency, despite its promising market potential. Social media marketing is proposed as an alternative strategy to reach a wider consumer base, with consideration of the varying levels of digital literacy among the local population. A quantitative approach with an explanatory research method was employed. Data were collected through an online questionnaire distributed to 100 consumers who had made purchases and were exposed to digital promotions. The analysis used Moderated Regression Analysis (MRA). The results indicate that social media marketing has a significant and positive effect on purchase decisions. Furthermore, digital literacy strengthens the relationship between social media marketing and consumer purchasing behavior. These findings suggest that the effectiveness of digital marketing strategies in limited markets is highly dependent on consumers’ readiness to access and interpret digital information. This study offers practical implications for local businesses to integrate social media promotions with efforts to improve consumer digital literacy in order to foster sustainable business growth.